2012
DOI: 10.4490/algae.2012.27.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Nereocystis luetkeana (Laminariales, Ochrophyta) and Eualaria fistulosa (Laminariales, Ochrophyta) spores to sedimentation

Abstract: The establishment of algal spores plays an essential role in adult kelp distribution and abundance patterns. Sedimentation is a key variable regulating algal spore settlement and success, possibly controlling species-specific dominance in situ. Laboratory experiments were used to determine spore attachment and survival rates of two Alaskan canopy-forming kelps, Nereocystis luetkeana (K. Mertens) Postels & Ruprecht and Eualaria fistulosa (Postels & Ruprecht) M. J. Wynne, to various types of sediment loading. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Chapman 1984, Connell & Russell 2010 by blocking spore settlement (Airoldi 2003, Deiman et al 2012 or creating an inimical microenvironment (reduced light, oxygen, or nutrients) for postsettlement survival of the early lifehistory stages of kelp (Daly & Mathieson 1977, Devinny & Volse 1978. As far as we are aware, our study is the first to document extensive macroscopic recruitment of kelp sporophytes to filamentous and coarsely branched turf algae in the northwest Atlantic.…”
Section: Recruitment and Persistence Of Kelp On Turf Algae And Rocky mentioning
confidence: 88%
See 2 more Smart Citations
“…Chapman 1984, Connell & Russell 2010 by blocking spore settlement (Airoldi 2003, Deiman et al 2012 or creating an inimical microenvironment (reduced light, oxygen, or nutrients) for postsettlement survival of the early lifehistory stages of kelp (Daly & Mathieson 1977, Devinny & Volse 1978. As far as we are aware, our study is the first to document extensive macroscopic recruitment of kelp sporophytes to filamentous and coarsely branched turf algae in the northwest Atlantic.…”
Section: Recruitment and Persistence Of Kelp On Turf Algae And Rocky mentioning
confidence: 88%
“…Once established, turf algae can physically inhibit settlement of kelp spores by entrapping sediment (Airoldi 2003, Deiman et al 2012) and reducing the availability of coralline-covered rock upon which kelp spores normally settle (N orton & Fetter 1981, Kennelly 1987. Some species of turf algae may also chemically alter the substrate, preventing settlement of kelp spores even after the turf is removed (Kennelly 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors that we did not explore may influence where the microscopic stages of bull kelp settle and complete their life stage transitions; for example, the effects of sedimentation as well as the combination of increased temperature and salinity may negatively influence the settlement and survival of microscopic stages (Deiman et al. , Lind and Konar ).…”
Section: Discussionmentioning
confidence: 99%
“…Zoospore release is a critical first step in the life cycle of kelps, and a prerequisite for culturing and studying their microscopic life stages. Our literature review revealed over 421 studies that utilized zoospore release protocols, with a strong bias toward ecological experiments testing zoospore and gametophyte performance under a range of environmental conditions (cf raw data provided on Dryad; see data availability statement) including temperature (Mabin, Gribben, Fischer, & Wright, ; Matson & Edwards, ; Mohring et al, ), UV radiation (Han & Kain, ; Huovinen, Oikari, Soimasuo, & Cherr, ), and sedimentation (Deiman, Iken, & Konar, ; Geange, Powell, Clemens‐Seely, & Cárdenas, ). This focus can likely be attributed to an interest in understanding the growing impacts of human activities on kelp forests.…”
Section: Discussionmentioning
confidence: 99%